Muskellunge Growth Potential in Northern Wisconsin: Implications for Trophy Management. (17th July 2015) - Faust, Matthew D.; Isermann, Daniel A.; Luehring, Mark A.; Hansen, Michael J.
Abstract: The growth potential of Muskellunge Esox masquinongy was evaluated by back‐calculating growth histories from cleithra removed from 305 fish collected during 1995–2011 to determine whether it was consistent with trophy management goals in northern Wisconsin. Female Muskellunge had a larger mean asymptotic length (49.8 in) than did males (43.4 in). Minimum ultimate size of female Muskellunge (45.0 in) equaled the 45.0‐in minimum length limit, but was less than the 50.0‐in minimum length limit used on Wisconsin's trophy waters, while the minimum ultimate size of male Muskellunge (34.0 in) was less than the statewide minimum length limit. Minimum reproductive sizes for both sexes were less than Wisconsin's trophy minimum length limits. Mean growth potential of female Muskellunge in northern Wisconsin appears to be sufficient for meeting trophy management objectives and angler expectations. Muskellunge in northern Wisconsin had similar growth potential to those in Ontario populations, but lower growth potential than Minnesota's populations, perhaps because of genetic and environmental differences.